Increase in diabetes among urban Alaska Native people in the Alaska EARTH follow-up study: A call for prediabetes screening, diagnosis, and referral for intervention. (September 2020) - Koller, Kathryn R.; Day, Gretchen E.; Hiratsuka, Vanessa Y.; Beans, Julie A.; Nash, Sarah H.; Redwood, Diana G.; Zhu, Jianhui; Howard, Barbara V.; Umans, Jason G.
Abstract: Aims: This study estimates incidence of diabetes (DM) and pre-DM relative to DM risk factors among relatively healthy Alaska Native and American Indian (henceforth AN) adults living in urban south central Alaska. Methods : Baseline (2004–2006) and follow-up (2014–2017) surveys, blood samples, and medical chart review data were collected from AN adults living in south central Alaska. We analyzed associations between prevalent risk factors and incident DM and pre-DM using Cox proportional hazards and used multivariable models to identify independent predictors for both DM and pre-DM. Results : Among 379 participants with follow-up data, overall DM incidence was 16.5/1, 000 PY; overall pre-DM incidence was 77.6/1, 000 PY, with marked differences between men and women. Prevalent cardiometabolic risk factors also varied with greater amounts of overweight in men and greater amounts of obesity in women. Controlling for age and sex, obesity, abdominal adiposity, pre-DM, and metabolic syndrome independently increased DM risk. Conclusion: Health care providers of AN populations must seize the opportunity to screen, refer, and treat individuals with pre-DM and other modifiable DM risk factors prior to DM diagnosis if we are to alter the epidemiologic course of disease progression in this urban AN population.